The Ethanol Extract of Fructus trichosanthis Promotes Fetal Hemoglobin Production via p38 MAPK Activation and ERK Inactivation in K562 Cells. (11th August 2011) - Li, Hui; Ko, Chun Hay; Tsang, Suk Ying; Leung, Ping Chung; Fung, Ming Chui; Fung, Kwok Pui
Abstract : Pharmacological stimulation of fetal hemoglobin (HbF) expression may be a promising approach for the treatment of beta-thalassemia. In this study, the effects of Fructus trichosanthis (FT) were investigated in human erythroleukemic K562 cells for their gamma-globin mRNA and HbF-induction activities. The role of signaling pathways, including extracellular regulated protein kinase (ERK) and p38 mitogen-activated protein kinase (MAPK), was also investigated. It was found that the ethanol extract of FT significantly increased gamma-globin mRNA and HbF levels, determined by real-time reverse transcription polymerase chain reaction and enzyme linked immunosorbent assay, respectively, in dose- and time-dependent manner. Total Hb (THb) levels were also elevated in the concentrations without cytotoxicity (<80 μ g mL −1 ). Pre-treatment with p38 MAPK inhibitor SB203580 blocked the stimulatory effects of FT extract in total and HbF induction. In contrast, no change in HbF was observed when treated with ERK inhibitor PD98059. Furthermore, FT ethanol extract activated p38 MAPK and inhibited ERK signaling pathways in K562 cells, as revealed in western blotting analysis. In addition, SB203580 significantly abolished p38 MAPK activation when the cells were treated with FT. In summary, the ethanol extract of FT was found to be a potent inducer of HbF synthesis in K562 cells. The present data delineated the role of ERK and p38 MAPK signaling as molecular targets for pharmacologic stimulation of HbF production upon FT treatment.